Systematic review examining the evidence for impact of school policies on physical activity. (30th September 2020) - Volf, K; Kelly, L; García Bengoechea, E; Gobis, A; Lakerveld, J; Zukowska, J; Gelius, P; Messing, S; Forberger, S; Woods, C
Abstract: Background: Epidemiological evidence has demonstrated that physical activity can have substantive health benefits for children and young people. The 'Policy Evaluation Network' is a multi-disciplinary research network across 7 European countries and New Zealand aimed at building capacity and evaluating the level of impact of policy interventions for promoting healthy lifestyles. The Toronto Charter identified 'whole-of-school' programmes as one of seven key investments for promotion of PA. This paper presents results of a SLR, designed to assess the level of evidence for policies within the school setting that contribute directly or indirectly to increasing PA. Methods: Researchers searched six online databases for scientific literature regarding PA policy interventions in the school setting using key concepts of policy, school, PA and evaluation. Risk of bias will be assessed with tools appropriate to the design of the studies considered. Evidence of actual or potential positive PA outcomes arising directly or indirectly from policy actions will be catalogued. Results: Preliminary searches identified 2327 unique scientific articles. 1938 (83.3%) were excluded on first reading and 189 (8.8%) were included for full text analysis. Initial findings suggest that organisational policies, for example avoiding overcrowding in playgrounds during school breaks, may be a promising policy action. Detailed analysis revealing other potential policy actions supported by evidence will be presented (SLR in progress). Conclusions: Preliminary findings suggest that few studies link policy actions in the school setting to PA outcomes. However, studies that have investigated the effects of changes to the school environment on PA levels may provide evidence for policy actions. Preliminary recommendations include strengthening the evidence base for school-based PA policy by supporting studies into the effects of particular policy or legislative changes on PA outcomes. Key messages: School physical activity policies are an underappreciated public health intervention. More studies should link policy changes to physical activity outcomes.